TOWARDS A SYNERGY BETWEEN DANCE PEDAGOGY AND PRAXIS FOR NATIONAL DEVELOPMENT - Odunze, Josephine Awele; Asigbo, Alex (ShodhKosh: Journal of Visual and Performing Arts, 2022)
The initial objective of dance education was to development the art form and harness its potentials for societal development. That dance education in Nigeria’s tertiary institutions of learning is largely seen as an isolated and purely academic exercise with little or no relevance to the real sector is hardly in contention as several studies attest to that reality. What is of concern is how to make it more relevant to the present milieu. Against universal trends, major developments in dance in Nigeria are driven by forces independent of academic influences. Various reasons have been advanced by scholars Ikideh (1987), Adeyemi (2010), Onyemuchara (2018) Onyemuchara, for instance, contends that the paucity of practice-based curriculum is the bane. Drawing from related disciplinary paradigms, this paper explores the possibility of synergizing the efforts of both the academic and professional/industry dance practitioners to make dance more relevant to national development.